EDUCATIONAL PEDAGOGY IN DISTANCE LEARNING ENVIRONMENTS (International Conference on Modern Science and Scientific Studies, 2025)
The introduction of modern information and communication technologies in the educational process has led to the creation of a new form of teaching –distance learning, in addition to traditional teaching methods.